Kontrol Informal dan Formal Terhadap Yakuza di Jepang - Fadli, Zaki Ainul; Nabila, Femiga Salsa (IZUMI, 2019)
(Title: Informal and Formal Controls Against Yakuza in Japan) This research explores how far yakuza's development in Japan and to find social factors which affecting its change. The methods used are literary research. This paper discusses the implementation of formal and informal social control in Japanese society and its ties to yakuza. The fact that yakuza, as Japanese mafia, have been intervening its society for decades, is a strange phenomenon since Japan is known for its low crimes as portrayed on most of the media. The formal control section will be focused on the National Police Agency of Japan, while the informal control section will be focused on Japanese society, emphasizing on its culture. Both controls leave the door open for yakuza to establish power in society. This may lead to the conclusion that Japan’s social control is relatively weak. gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor